Affect and artificial intelligence - Wilson, Elizabeth A. (Elizabeth Ann), 1964- (In vivo (Seattle, Wash.), 2010)
"In 1950, Alan Turing, the British mathematician, cryptographer, and computer pioneer, looked to the future: now that the conceptual and technical parameters for electronic brains had been established, what kind of intelligence could be built? Should machine intelligence mimic the abstract thinking of a chess player or should it be more like the developing mind of a child? Should an intelligent agent only think, or should it also learn, feel, and grow?" "Affect and Artificial Intelligence is the first in-depth analysis of affect and intersubjectivity in the computational sciences. Elizabeth Wilson makes use of archival and unpublished material from the early years of artificial intelligence (1945-70) until the present to show that early researchers were more engaged with questions of emotion than many commentators have assumed. She documents how affectivity was managed in the canonical works of Walter Pitts in the 1940s and of Turing in the 1950s, in projects from the 1960s that injected artificial agents into psychotherapeutic encounters, in chess-playing machines from the 1940s to the present, and in the Kismet (sociable robotics) project at MIT in the 1990s." ""In this fresh and provocative contribution to affect studies, Elizabeth Wilson convincingly argues that from its beginnings the theory and practice of artificial intelligence has been decisively marked by feelings---surprise, curiosity, delight, shame, and contempt---as well as computational logic. She suggests, with wonderful wit and a fine intelligence, that interiority is conjugated by positive and passionate affects of attachment as well as cognitive circuits among humans and machines.""--Jacket.